Pengembangan Lembar Kerja Peserta Didik Berorientasi Model Pembelajaran Problem Based Learning Pada Materi Musyawarah Untuk Siswa Kelas Iv Sdn 39 Pontianak Kota : Pengabdian - Soniya Yunyun; Siti Halidjah; Rio Pranata (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to develop a student worksheet (LKPD) oriented toward the Problem-Based Learning (PBL) model to support Civics Education (PPKn) in the topic of deliberation for Grade IV students at SDN 39 Pontianak Kota. The research uses a Research and Development (R&D) approach by adapting the ADDIE model, involving 27 students, one classroom teacher, and three expert validators. Data were collected through interviews and questionnaires. The development process followed four stages: Analysis, Design, Development, and Implementation. The validity results showed that the design aspect scored 88.00%, the language aspect 95.00%, and the material aspect 91.66%, all categorized as “Highly Valid.” Furthermore, the practicality of the LKPD was rated at 90.06%, falling under the “Highly Practical” category. These results indicate that the developed PBL-oriented LKPD is both valid and practical for use in supporting effective learning in Civics Education for elementary school.